Manajemen Marketing Madrasah Melalui Teknologi Informasi Dan Komunikasi di MA Hidayatul Mubtadiin Jati Agung Lampung Selatan - Nur Hayati; Nurul Hidayati Murtafiah; Etika Pujianti (Departement of Mathematics Education, 2024)
The point of this examination is to decide and break down the preparation, execution and assessment of madrasa showcasing the executives through data and correspondence innovation at Madrasah Aliyah Hidayatul Mubtadiin Jati Agung South Lampung. This sort of exploration is subjective examination, the technique utilized in this exploration utilizes perception, meetings and documentation. The information sources in this examination are essential and optional exploration sources. The information investigation procedure utilized is an intuitive model and information triangulation to really look at the legitimacy of the information. The exploration results show that 1) Mama Hidayatul Mubtadiin's new understudy confirmations advertising arranging (PPDB) is the most vital phase in the understudy affirmations process. The initial step is vital, on the grounds that the initial step is important for the interaction that will prompt the eventual outcome. Figuring out a promoting program execution plan zeros in additional on tips, strategies, procedures or methodologies that are successful, effective and adaptable to carry out. Execution arranging should think about time distribution, accessibility of assets, HR, offices, etc. 2) Execution of Mama Hidayatul Muntadiin's showcasing through data and correspondence innovation by carrying out a blend, in particular item, value, spot and advancement. In the interim, the media utilized for madrasa advertising are handouts and the web like sites, WA, Instagram, Facebook, TV and papers. 3) Assess the advertising system or execution associated with showcasing, by taking a gander at the degree of promoting exercises that have been carried out, by proceeding with exercises that have been generally answered by the general population.